Hi there!
Your equation states 7(2a - 3) - 5a = -3
The first step is to simplify the parentheses. When they are touching a number like that, or in your case number 7, it means multiplication.
7(2a - 3)
Start multiplying
7 × 2a = 14a.
7 × (-3) = -21
Now combine the answers and then the equation.
14a - 21 - 5a = -3
Add 21 to both sides
14a - 21 - 5a = -3
+ 21 +21
You will be left with 14a - 5a = 18
Subtract 14a - 5a
That will equal 9a
9a = 18
Divide 9 from both sides.
9 ÷ 9, you will be left with a.
9 ÷ 18 would equal 2.
Your answer would be a = 2
Hope this helped!~